Local R&D and technology transfers: A Comparative Analysis of foreign and local firms in Indian Industries - Aradhna Aggarwal (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
This study examines how inter-firm heterogeneities in technology modes and intensities are linked to ownership of firms in India, using a panel dataset of 2000 odd Bombay Stock Exchange listed firms for the period from 2003 to 2014 drawn from the PROWESS database of CMIE. For the analysis, foreign ownership is categorised according to the control exercisable by them as defined under the Companies' Act of India. A comparative analysis of domestic and different categories of foreign firms was conducted at two time periods: the global boom period of 2004-2008 and post crisis period of 2008-2014. The propensity score matching (PSM) analysis reveals that the majority owned foreign companies spend less on R&D and more on technology transfers than their local counterparts. Overall, threshold equity holding and global conditions matter. A panel data regression analysis on matched sample confirms the findings and validates the PSM findings. A horizontal cluster analysis on 3-digit industry level data shows that foreign firms cluster in high technology industries.
hdl:10398/9293
Keywords: 330; Foreign firms; Majority owned foreign subsidiariesminority owned subsidiaries; Domestic firms; Performance; Eigentümerstruktur; Multinationales Unternehmen; Tochtergesellschaft; Industrieforschung; Technologietransfer; Indien